The Influence Of Transformational Leadership And Human Resource Management (HRM) On The Performance Of Employees At The Pekanbaru City Education Office - Nurman, Nova; Marhadi, Hendri; Mustafa, Nur (Lembaga Riset dan Inovasi Almatani, 2025)
This study concludes that transformational leadership and human resource management (HRM) significantly enhance employee performance at the Pekanbaru City Education Office. Transformational leadership—reflected through idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—effectively improves the quality, quantity, and punctuality of employee work by providing role modeling, inspiration, and intellectual empowerment. Meanwhile, professionally implemented HRM practices, including planning, recruitment, competency development, compensation, and performance evaluation, contribute substantially to strengthening employee motivation, effectiveness, and productivity. Together, these two factors mutually reinforce one another: transformational leadership offers direction and momentum for change, while HRM provides a supportive system that enables employee development. Collectively, they cultivate an innovative, competitive organizational culture oriented toward enhancing the quality of public services.